Price Dynamics in Central and Eastern European EU Accession - Peter Backé; Jarko Fidrmuc; Thomas Reininger; Franz Schardax (Oesterreichische Nationalbank (OeNB), 2002)
In this paper we review the developments of prices in the Central and Eastern European EU accession countries between 1990 and 2001. The paper starts with an analysis of the short-term and long-term (dis)inflation dynamics. This is complemented by an appraisal of price level convergence. The major driving forces of price formation in the accession countries are found to be related to price liberalization during the transition to a market economy, to the prospective EU accession, and to the catching-up process (Balassa-Samuelson effect). Finally, the paper draws conclusions about future monetary and exchange rate policy options in the run-up to EU accession and beyond.
Keywords: E31; E42; F41; 330; Price liberalization; core inflation; Balassa-Samuelson effect; EU enlargement